2013
DOI: 10.1126/science.1227166
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Oxidative Stress by β-Hydroxybutyrate, an Endogenous Histone Deacetylase Inhibitor

Abstract: Concentrations of acetyl–coenzyme A and nicotinamide adenine dinucleotide (NAD+) affect histone acetylation and thereby couple cellular metabolic status and transcriptional regulation. We report that the ketone body d-β-hydroxybutyrate (βOHB) is an endogenous and specific inhibitor of class I histone deacetylases (HDACs). Administration of exogenous βOHB, or fasting or calorie restriction, two conditions associated with increased βOHB abundance, all increased global histone acetylation in mouse tissues. Inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
1,146
7
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,418 publications
(1,265 citation statements)
references
References 26 publications
42
1,146
7
6
Order By: Relevance
“…Because butyrate and its derivatives have been shown to protect against oxidative stress by modulating antioxidant enzyme activity (Shimazu et al ., 2013), we tested the effect of aging and butyrate on antioxidant and detoxification enzyme and stress–response protein levels using quantitative mass spectrometry. A significant effect of age was found for eight antioxidant enzymes (Table 2), and a significant effect of diet was observed for two enzymes: catalase and glutathione S‐transferase P. An interaction between age and diet was found for catalase, so we sought to clarify the effect of butyrate and age on catalase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because butyrate and its derivatives have been shown to protect against oxidative stress by modulating antioxidant enzyme activity (Shimazu et al ., 2013), we tested the effect of aging and butyrate on antioxidant and detoxification enzyme and stress–response protein levels using quantitative mass spectrometry. A significant effect of age was found for eight antioxidant enzymes (Table 2), and a significant effect of diet was observed for two enzymes: catalase and glutathione S‐transferase P. An interaction between age and diet was found for catalase, so we sought to clarify the effect of butyrate and age on catalase.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported elevated antioxidant enzyme activity from treatment with butyrate and HDAC inhibitors (Kang et al ., 2002; Shimazu et al ., 2013). Consistent with this, we found that butyrate prevented oxidative damage to proteins during aging and increased catalase activity in muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3HB is an endogenous HDAC inhibitor (Shimazu et al., 2013), and the inhibition of HDAC leads to the activation of the Nrf2 pathway (Wang et al., 2012), promoting protection against neuronal damage. Acetylation levels of histone H3, K9, K14, and K27 in the IF and 3HB groups were similar to those in the AL group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of a limiting enzyme of 3HB synthesis, mitochondrial hydroxymethylglutaryl‐CoA synthase (mHMG‐CoAS), is regulated through deacetylation by Sirt3 (Shimazu et al., 2010) and mTOR (Sengupta et al., 2010), master regulators of energy metabolic homeostasis signaling, and these activities have been linked to ameliorating diseases associated with oxidative stress. A more recent finding also showed that 3HB is an endogenous histone diacetyl‐lase inhibitor that helps cells resist oxidative stress (Shimazu et al., 2013). Furthermore, endogenous 3HB inhibits the activation of the NLRP3 inflammasome in macrophages, which is linked to chronic anti‐inflammatory effects (Youm et al., 2015).…”
Section: Introductionmentioning
confidence: 99%